2017
DOI: 10.1111/ejed.12216
|View full text |Cite
|
Sign up to set email alerts
|

Education policy in Poland: The impact of PISA (and other international studies)

Abstract: The impact of the PISA study on Polish education policy has been significant, but probably different from any other country. Poland has not experienced the so‐called ‘PISA shock’, but its education system has been benefiting considerably from PISA. For experts and policy makers, it has been a useful and reliable instrument that has made it possible to measure the effects of consecutive reforms of the school education system. Moreover, PISA and other international studies have influenced the perception of educa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 8 publications
0
17
0
2
Order By: Relevance
“…In this way, the purpose of the competences has not been to redesign the teaching and learning processes, but to meet the European guidelines. As a consequence of this superficial fit, the subject areas and the assessment standards continue focused on the contents of school subjects and not on the competences [28][29][30][31][32][33]. The last Spanish educational law in 2013 [2] reduced the role of key competences even more, compared to the legislation of 2006 [1], conceiving them more as capacities than as features applicable to all disciplines [34].…”
Section: C2 Wordsmentioning
confidence: 99%
“…In this way, the purpose of the competences has not been to redesign the teaching and learning processes, but to meet the European guidelines. As a consequence of this superficial fit, the subject areas and the assessment standards continue focused on the contents of school subjects and not on the competences [28][29][30][31][32][33]. The last Spanish educational law in 2013 [2] reduced the role of key competences even more, compared to the legislation of 2006 [1], conceiving them more as capacities than as features applicable to all disciplines [34].…”
Section: C2 Wordsmentioning
confidence: 99%
“…A. Tiana Ferrer, whilst mentioning the reception of PISA by the media in Spain, insists more on its impact in the political discourse and analyses to what extent some major education reforms can be related to some PISA results and OECD recommendations (Tiana Ferrer, 2017). It is also the case of the German researchers who analyse the PISA shock in Germany and the diversity of policy reactions, depending on each Land in this federal context (Martens & Niemann, 2013;Martens, Niemann & Teltemann, 2017), and the article about the major changes in Poland which were largely enhanced by the poor results of the first PISA surveys (Bialecki, Jakubowski & Wisniewski, 2017).…”
Section: Pisa As a G Rowing Factor Of Evidence-based Educ At Ion Pomentioning
confidence: 99%
“…According to some authors, the OECD, through its policy recommendations and examples of 'good practice', has established a new type of 'soft governance' of education systems (Bieber & Martens, 2011;Lingard & Sellar, 2013) or a global educational governance (Meyer & Benavot, 2013). Several authors have observed a direct influence of PISA on educational reforms (Bialecki, Jakubowski, & Wisniewski, 2017;Breakspear, 2012;Grek, 2009Grek, , 2010Martens, Nagel, Windzio, & Weymann, 2010;Niemann, Martens, & Teltemann, 2017). Within Europe, it has been generally recognised that, in some countries, some important reforms have been presented and justified in relationship with PISA results: it is particularly the case of Germany, Denmark, Poland, Portugal and Switzerland for example, and to less extent of Spain, The Netherlands or England and Wales.…”
Section: The I Nfluence Of Pisa On Education P Olicies: the Di F F mentioning
confidence: 99%
“…Centralization may be an answer on problems brought by crises like in the case of Greece (Tsekos T. N. and Triantafyllopoulou A., 2016) and Hungary, or on effects of political turn like in Poland (Białecki, I., Jakubowski, M., Wiśniewski, J., 2017) in 2010s. Our hypothesis is that both of the two directions originate in economic reasons.…”
Section: Introductionmentioning
confidence: 99%